On the Evaluation of the Remainder Term in the Central Limit Theorem for the Sum ∑φ(2^j t) - Misevičius, G. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Г. Мисявичус. Об оценке остаточного члена в центральной предельной теореме для сумм вида ∑φ(2^j t)G. Misevičius. Apie liekamojo nario įvertinimą ∑φ(2^j t) pavidalo sumų centrinėje ribinėje teoremoje